Antimicrobial effect of areca nut ethanol extract against methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive Staphylococcus aureus (MSSA) - Hanina Hanina; Humaryanto Humaryanto; Lipinwati Lipinwati (Riset Informasi Kesehatan, 2023)
Background: Developing herbal medicines for antibacterial activity has been challenging in Indonesia. Of the alternative antimicrobials, areca nut (Areca catechu L) has antimicrobial activity since it contains flavonoids, tannins, phenols, alkaloids, saponins, terpenoids, and glycosides. The use of antibiotics in underdeveloped and developing countries is still irrational, and bacterial infection in Indonesia is still a problem to resolve, so searching for new herbal medicines is very important. Staphylococcus aureus is the most common normal flora that causes infection. The two types of Staphylococcus aureus are Methicillin-resistant Staphylococcus aureus (MRSA) and Methicillin-sensitive Staphylococcus aureus (MSSA). The study aimed to determine the efficacy of the antibacterial activity of areca nut ethanol extract against MRSA and MSSA isolates. Methods: The research was conducted at the Biomedical Laboratory, Faculty of Medicine and Health Sciences, University of Jambi. Young and old areca nut ethanol extracts were macerated using 96% ethanol. The antibacterial activity test of the ethanol extract was carried out using the Kirby-Bauer disc diffusion method against the isolates of MRSA (clinical isolates) and MSSA (SA 25923/K+, SA 29213/K-). Results: The results showed that the phytochemicals of young areca nut extracts contained alkaloids, flavonoids, phenols, and steroids, and old areca nut extracts contained alkaloids, flavonoids, and phenols. The MRSA isolates did not show the activity of the two areca nut ethanol extracts and were also resistant to Ceftadizime, Gentamicin, Ceftriaxone, and Cefoxitin. The MSSA isolates showed strong activity against old areca nut ethanol extract, moderate activity against young areca nut ethanol extract, and resistance to gentamicin. Conclusion: MRSA bacteria are resistant to the ethanol extract of young and old areca nuts, while the ethanol extract of old areca nuts has strong antibacterial activity against MSSA. Keywords: antibacterial, areca seed ethanol extract, MRSA, MSSA